2005
DOI: 10.1360/982005-186
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on electrical breakdown field strength of electrode with water mist containing MC additives

Abstract: Water mist is one of the effective candidates for halon replacement used in electrical environment fire protection. Water mist additives may greatly enhance fire suppression effectiveness. In electrical environment, electrical breakdown field strength (E) is one of the important factors that control the performance of electrical equipment. In this study the variation principles of electrical breakdown field strength and the electrical characteristics of MC additives were investigated by electrode discharging e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The reason is that the high temperatures [almost 1.45×10 4 K (Cheng et al, 2010)], heat exchanges and particle densities in the intermittent zone have been greatly reduced, the gap is not much different from that of pure air. Meanwhile, it is also proved that the average breakdown field strength decreases with the increase of distance in air (Fang et al, 2005;Yu-Chien et al, 2019).…”
Section: Breakdown Mechanisms and Influencing Factors Of Wire-wire Gapsmentioning
confidence: 95%
“…The reason is that the high temperatures [almost 1.45×10 4 K (Cheng et al, 2010)], heat exchanges and particle densities in the intermittent zone have been greatly reduced, the gap is not much different from that of pure air. Meanwhile, it is also proved that the average breakdown field strength decreases with the increase of distance in air (Fang et al, 2005;Yu-Chien et al, 2019).…”
Section: Breakdown Mechanisms and Influencing Factors Of Wire-wire Gapsmentioning
confidence: 95%
“…Under the same water pressure, an increase in height leads to improved sprinkling uniformity. Several studies [20][21][22][23][24] suggested that the water mist environment generated during the rain test could be simulated using a spray tower stand. Conducting experimental research in this context can yield data on rainfall intensity and sprinkling uniformity.…”
Section: Icmsoa-2023mentioning
confidence: 99%